Natural convection and entropy generation of a nanofluid in two connected inclined triangular enclosures under magnetic field effects. (November 2019) - Liu, Wi; Shahsavar, Amin; Barzinjy, Azeez A.; Al-Rashed, Abdullah A.A.A.; Afrand, Masoud
Abstract: The objective of this paper is to study the entropy generation and natural convection of water- Al2O3 nanofluid in an inclined cavity which consists of two connected inclined triangular enclosures under a horizontal magnetic field. The horizontal diameter of the cavity is small in thickness and has the temperature Tc. Half of the bottom wall and also the right wall are at the temperature Th. The rest of the walls are adiabatic. The governing equations of the nanofluid flow are algebrized and solved using the FVFEM method. The effective parameters are 103<Ra<105, 0<Ha<40, 0°<γ<90°, and 0.00<φ<0.06. The results indicate that the rate of heat transfer increases by 12% and the entropy generation enhances by 13% through enhancing the Raleigh number. As the Hartmann number increases, the rate of heat transfer and the entropy generation decrease by 6.5% and 8%, respectively. The Bejan number also decreases for a higher Raleigh number and a lower Hartmann number. For a higher angle of the cavity, the average Nusselt number calculated on the right wall always reduces. Entropy generation decreases and Bejan number increases for a higher inclined angle.